Multimedia in Translation Class: A Technology Acceptance Model - Refika Andriani; Herdi Herdi; Destina Kasriyati (Journal of English Culture, Language, Literature and Education, 2023)
In the era of revolution industry, it is believed that the integration of technology in the language learning activity widely increase. The purpose of the research was to investigate the implementation of multimedia as technology integrated in the Translation course learning activity. A quantitative approach is employed in this study with 47 students from English Education Department of Univesitas Lancang Kuning selected by using total sampling technique. This research was descriptive quantitative using survey design. The data collected by using a Likert Scale questionnaire with three indicators of Technology Acceptance Model (TAM) namely perceived usefulness, perceived ease of use, and attitude toward using. After that, the data was analysed by using descriptive statistic. Overall, it was found that the statistical data of multimedia implementation in the Translation course is about 3.99. It is claimed into “moderate” category. It indicates that the multimedia implementation in the Translation course helps the students to be more confident during the class. It also makes students enjoy the learning process. Multimedia also made the learning process become effective and efficient